Efektivitas Program Kartu Prakerja dalam Membangun Sumberdaya Manusia - Siti Dwi Yana (FEBI IAIN Langsa, 2021)
This writing discusses the effectiveness of the Pre-Work program in building human resources and the role of the Pre-employment program in building the quality of human resources. The objectives of this study were to: (1). Determine the effectiveness of the Pre-employment program in building resources amid the human pandemic. (2). Determine the role of the Pre-employment program in building the quality of human resources in the midst of a pandemic. By using a descriptive qualitative research approach, the type of data used in this study is primary data obtained from in-depth interviews with community recipients of the pre-work card program assistance. The research results obtained are: (1). Pre-employment programs are less effective in building human resources. (2). The Pre-employment Program plays a very important role in building the quality of human resources.